Swimmer’s Itch (Cercarial Dermatitis) - Emma N. I. Weeks; Katherine Sayler; Heather Stockdfale Walden (EDIS)
Learn how to swim safely and avoid this itchy skin rash in this 3-page document written by Emma N. I. Weeks and Katherine Sayler and published by the UF/IFAS Department of Entomology and Nematology. Updated May 2022 with Heather Stockdale Walden. https://edis.ifas.ufl.edu/in1200